2007
DOI: 10.1002/adic.200790104
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of Aluminium and Iron with Hematoxylin Using Spectrophotometric and Orthogonal Signal Correction‐Partial Least Squares in Plant and Water

Abstract: Simple and novel spectrophotometric method is described for simultaneous determination of aluminum and iron. The method is based on the colored complexes formed by aluminum and iron with hematoxylin in the presence of cetyltrimethylammonium bromide as a surfactant at pH 5.8. All factors affecting the sensitivity were optimized and the linear dynamic range for determination of aluminum and iron was found. The simultaneous determination of aluminum and iron mixtures by using spectrophotometric methods is a diffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Utilities of electrode sensors have developed to use in different ways [7][8][9]. Many techniques, like, atomic absorption spectrometry; AAS [10][11][12][13][14][15][16], spectro-fluorometry [17,18], chromatography [19][20][21][22], a laser diode atomic absorption spectroscopy [23], inductively coupled plasma-atomic emission spectrometry; ICP-AES [24][25][26], inductively coupled plasma-mass spectra; ICP/MS [27][28][29][30], spectrophotometry based on use of various reagents [31][32][33][34][35][36][37][38][39][40][41], ion-selective electrode techniques [42][43][44][45][46][47][48][49][50][51][52] and other recently different methods [53]…”
Section: Introductionmentioning
confidence: 99%
“…Utilities of electrode sensors have developed to use in different ways [7][8][9]. Many techniques, like, atomic absorption spectrometry; AAS [10][11][12][13][14][15][16], spectro-fluorometry [17,18], chromatography [19][20][21][22], a laser diode atomic absorption spectroscopy [23], inductively coupled plasma-atomic emission spectrometry; ICP-AES [24][25][26], inductively coupled plasma-mass spectra; ICP/MS [27][28][29][30], spectrophotometry based on use of various reagents [31][32][33][34][35][36][37][38][39][40][41], ion-selective electrode techniques [42][43][44][45][46][47][48][49][50][51][52] and other recently different methods [53]…”
Section: Introductionmentioning
confidence: 99%
“…Aluminium, present in most industrial effluents discharges and in domestic wastes and wastewater, is also found in over the counter medicines, such as antacids and buffered aspirins, is used as a food additive, and is found in a number of topically applied consumer products such as antiperspirants, first aid antibiotic and antiseptics [3] . All these findings cause alarming concerns in public health, demanding accurate determination of this metal ion at traces and sub-trace levels.…”
Section: Introductionmentioning
confidence: 99%